2020
DOI: 10.1088/1361-6463/ab83c3
|View full text |Cite
|
Sign up to set email alerts
|

Polarization driven self-biased and enhanced UV–visible photodetector characteristics of ferroelectric thin film

Abstract: BiFeO 3 is a promising multifunctional material in terms of its intriguing physics and diverse application potential. In this work, self-powered UV-visible photodetector characteristics of the polycrystalline BiFeO 3 thin film exhibiting pronounced photo-response under both UV and visible light are demonstrated. Interestingly, the film displays switchable photodetector characteristics in accordance with the polarization switching properties and thereby confirms the role of polarization driven depolarization fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…As shown in Table 1, overall performances of the Au/ZnO/PLZT/ FTO device in upward poling state are also significantly superior to those of the other ferroelectric-based self-powered UV detectors reported so far in literature. [7,8,[11][12][13]17,[44][45][46][47][48][49][50] This can be attributed to following factors: I) energy level alignments in the Au/ZnO/PLZT/FTO device are in favor of the separation and transport of photogenerated carriers; II) the beneficial coupling of the E dp and E ZnO/PLZT makes the photogenerated carriers separation and transportation much more efficient; III) the ZnO semiconductor layer also produces abundant photogenerated carriers under UV light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 1, overall performances of the Au/ZnO/PLZT/ FTO device in upward poling state are also significantly superior to those of the other ferroelectric-based self-powered UV detectors reported so far in literature. [7,8,[11][12][13]17,[44][45][46][47][48][49][50] This can be attributed to following factors: I) energy level alignments in the Au/ZnO/PLZT/FTO device are in favor of the separation and transport of photogenerated carriers; II) the beneficial coupling of the E dp and E ZnO/PLZT makes the photogenerated carriers separation and transportation much more efficient; III) the ZnO semiconductor layer also produces abundant photogenerated carriers under UV light illumination.…”
Section: Resultsmentioning
confidence: 99%
“…The response time which is the time taken for the current to reach 90% of its maximum value from its 10% is 0.27 s. The obtained value is comparable to the reported values for other ferroelectric system. 32,33 The photo-current, I ph , is calculated from the plot Fig. 5(c The resultant I ph displayed against the light intensities in Fig.…”
Section: Self-powered Photo-detector Charecteristicsmentioning
confidence: 99%
“…The tting reveals that q $ 0.97 and it shows better photocurrent capabilities of DIPAB lm compared to other ferroelectric photodetectors. 32,34 However, the deviation from the ideal value could be attributed to the recombination states and carrier-carrier interactions of the photogenerated carriers. To elucidate it further, the photodetector characteristic parameters such as the responsivity (R) and detectivity (D) are calculated from R ¼ I ph /PS and D ¼ R/(2eI d /S) 0.5 , where S is light illuminated area of the sample and e is the charge.…”
Section: Self-powered Photo-detector Charecteristicsmentioning
confidence: 99%
“…Recent research has revealed that ferroelectric materials have promising applications in new solar cells, photodetectors and photovoltaic memory devices. [23][24][25][26] This can be mainly explained by their bandgap-independent open-circuit voltage and the generation mechanism of photogenerated carriers. In ferroelectric-based self-powered photodetectors, there are two main mechanisms driving the separation of photogenerated electronhole pairs: the depolarization field and Schottky barrier formed between the ferroelectric material and the metal electrode.…”
Section: Introductionmentioning
confidence: 99%